Implementation of a road traffic crash injury surveillance tool in a trauma referral hospital in Kisumu City, Western Kenya: Lessons learned from the pilot study. (10th October 2022) - Radan, Bojana; Ogendi, Japheths; Charyk Stewart, Tanya; Shkrum, Michael
Abstract: Objective: Road traffic injury (RTI) is a major public health concern in Kenya with more than 13, 000 deaths estimated annually. The primary objective of this study was to design and implement an injury surveillance tool for the collection of injury data, and assess the tool's feasibility for the development of a hospital-based trauma registry in a leading Kenyan referral hospital. Secondarily, an epidemiologic profile was created to characterize RTI in the region. Methods: An injury surveillance tool was developed and implemented, on a pilot basis, in a level 5 trauma hospital, Jaramogi Oginga Odinga Teaching and Referral Hospital (JOOTRH), in Kisumu City, Western Kenya, for a 4-week period from 2019-07-15 to 2019-08-11. A descriptive statistical analysis summarized injury frequency counts and percentages. Results: Over the pilot phase, 371 patients had forms completed, but 488 official injury-related hospital registrations, indicating that 117 injury patients (24%) were missed. A process evaluation of the tool implementation revealed issues in the collection protocol that required revisions, resulting in improved data form completeness rates. For the 368 cases with cause documented, the most common mechanisms of injury were RTI (46.5%; n  = 171), assaults (23.9%; n  = 88), and falls (14.9%; n  = 55). For RTI patients, the median age was 28 years (IQR = 16) and 77% ( n  = 132) were males, with motorbike collision injuries ( n  = 91; 53.2%) the leading RTI mechanism. There were 348 injuries for 171 patients. The most common anatomical regions for RTI were the lower limb 32.8% ( n  = 114), upper limb (15.2%; n  = 53), followed by head lacerations 8.6% ( n  = 30) and concussions 7.2% ( n  = 25). Two-thirds of patients ( n  = 113; 66.1%) were discharged from ED, just over a quarter ( n  = 46; 26.9%) were admitted to hospital and 9 patients succumbed to RTI (5.3%). Conclusions: This injury surveillance pilot study produced the first injury dataset in Kisumu City, demonstrating the significant magnitude of RTI in Western Kenya, the leading cause of injury for the region. This dataset can be replicated in other hospitals to create an injury surveillance system for the collection of trauma data, needed for the development of countermeasures for the reduction of trauma, as well as for quality initiatives to improve patient outcomes.